Cross-reactivity to Kynureninase Tolerizes B Cells that Express the HIV-1 Broadly Neutralizing Antibody 2F5 - Finney, Joel (J Immunol, 2019)
2F5 is an HIV-1 broadly neutralizing antibody (bnAb) that also binds the autoantigens kynureninase and anionic lipids. Generation of 2F5-like Abs is proscribed by immune tolerance, but it is unclear which auto-specificity is responsible. We sampled the BCR repertoire of 2F5 knock-in mice before and after the first and second tolerance checkpoints. Nearly all small pre-B (pre-checkpoint) and 35–70% of anergic peripheral B cells (post-checkpoint) expressed the 2F5 BCR and maintained kynureninase-, lipid-, and HIV-1 gp41-reactivity. In contrast, all post-checkpoint mature follicular (MF) B cells had undergone light-chain editing that purged kynureninase- and gp41-binding but left lipid-reactivity largely intact. We conclude that specificity for kynureninase is the primary driver of tolerization of 2F5-expressing B cells. The MF and anergic B cell populations favored distinct collections of editor light chains; surprisingly, however, MF and anergic B cells also frequently expressed identical BCRs. These results imply that BCR autoreactivity is the primary determinant of whether a developing B cell enters the MF or anergic compartments, with a secondary role for stochastic factors that slightly “mix” the two pools. Our study provides mechanistic insights into how immunological tolerance impairs humoral responses to HIV-1, and supports activation of anergic B cells as a potential method for HIV-1 vaccination.